2007
DOI: 10.1007/s11199-007-9332-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Video Game Playing Habits and Visual Memory Tasks

Abstract: The current research examined whether visuospatial recall of both abstract and common objects was related to gender or object familiarity. Seventy two undergraduates from a university in the Southern U.S. were asked to draw the Rey Complex Figure and a series of common objects from memory. A pilot sample of seventy three undergraduates had previously identified common objects as "male" "female" and "neutral" exemplars. Males were significantly better at drawing "male" and "neutral" exemplars whereas females we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 23 publications
0
21
1
3
Order By: Relevance
“…Other studies have shown that playing video games results in improved visual memory. A study on 72 undergraduate students found that time spent playing video games was a predictor of improved visual memory [37]. A randomized study of 36 elderly nursing home residents consisted of 3 months of intensive virtual reality training followed by 3 months of periodic booster sessions [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that playing video games results in improved visual memory. A study on 72 undergraduate students found that time spent playing video games was a predictor of improved visual memory [37]. A randomized study of 36 elderly nursing home residents consisted of 3 months of intensive virtual reality training followed by 3 months of periodic booster sessions [38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have focused on how video game play may enhance some of these skills in a normal population. There is evidence that individuals who are avid video game players show enhanced visual attention skills (Green & Bavelier, 2003) and visual memory (Ferguson, Cruz, & Rueda, 2008). There is also causal evidence that nonplayers trained on video games show improved visual skills (Green & Bavelier, 2003, 2007.…”
Section: Commercially Available Video Games In Medical Educationmentioning
confidence: 99%
“…Deux (1985) also states that men outperform women in decoding visual stimuli. While it has been commonly held that males show an advantage on spatial tasks, and females on verbal tasks, Ferguson, et al (2007) suggest that male performance on visuo-spatial is more than female performance. Another study conducted by Leopold (2006) confirms that males and females use different parts of brain in language and visuo-spatial tasks.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 95%